New evidence on son preference among immigrant households in the United States - Huiqiong Duan; Daniel L. Hicks (IZA Journal of Development and Migration, 2020)
This paper provides new evidence on the acquisition and persistence of child gender preference among immigrant populations in the United States using Census and American Community Survey data. We first confirm the existing evidence of son preference among immigrant populations from South East Asia that was documented across multiple studies and samples. We then demonstrate several new empirical findings. First, Japanese immigrants exhibit daughter preference. Second, assortative matching between immigrant parents is associated with stronger gender preferences. Third, comparing male and female migrants who marry natives provides suggestive evidence that paternal preferences could be more to blame for son preference than maternal. Fourth, child gender preferences are strongest for migrants who arrive after childhood but do not appear to diminish with the duration of residence in the United States. Finally, while higher-order generations exhibit weaker son preference, there is a high degree of heterogeneity across groups. Most of the second- and higher-order generation immigrants assimilate more rapidly to US norms except Indian immigrant populations, which exhibit strong son preference among higher-order generations.
Keywords: J13; J15; J16; Z10; 330; son preference; immigrants; assimilation